Leolinda Daltro – the oaci-zauré – report of her experience in proposing secular education for indigenous people in central Brazil - Cunha dos Santos, Paulete Maria (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2016)
Leolinda de Figueiredo Daltro’s report of her experience among the Indians in the hinterlands of Goiás (Central-Western Brazil) and the proposal to create an association for protecting the indigenous people, which she disseminated widely in diverse social spaces after her return to Rio de Janeiro,raises some interesting issues. What did she know or had read about the indigenous way of life before her experience with them? What did she know about the policies adopted by the Republic in relation to the indigenous population? Or what did she know about the area in Central Brazil which she traversed? These are the questions that will be addressed throughout the text in order to explore more deeply the reactions on her return to the Federal Capital. We believe it is also important to understand how Leolinda got involved in the “indigenous cause” and how a proposal for indigenous secular education managed to evoke such a strong public response. This single episode experienced by Leolinda – as recorded in her book Da catechese dos indios no Brasil – offers several clues about her mission – in the city and in the hinterlands – and the numerous facets of the regional and national society networks that got her involved and committed.